Ergonomic Workstation Design for Fish Smoking Workers in the Coastal Area of Surabaya - Dani Nasirul Haqi; Putri Ayuni Alayyannur (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Workstation design should be made adjusting the workers’ anthropometry to not put additionalburden on the worker’s body. Fish smoking workers in the coastal area of Surabaya work sitting on a chairas high as their heels which cause them working with unnatural postures. This study aimed to determineergonomic workstation design for fish smoking workers in the coastal area of Surabaya.Methods: Respondents were the total population consisting of 12 male and 18 female workers. The worker’sbody was measured in a sitting position using a measuring tape. Dimensions measured included the reach ofthe thumb as measured from the back, elbow height when seated, calf height, hip width, buttock-popliteallength, and sitting height. Each dimension was calculated on the 5th and 95th percentiles to determine thesize of the ergonomic workstation.Result: Workstations were made with an adjustable concept. The size of the ergonomic workstation designfor male workers includes table width 71.93-77.57 cm, table height 51.81-55.86 cm, chair height 28.64-32.03 cm, chair width 38.66-41.84 cm, chair length 43.24-50.10 cm, and chairback height 89.21-95.46 cm.In addition, for female workers, the size of the ergonomic workstation design includes table width 60.55-68.00 cm, table height 39.21-43.57 cm, chair height 23.64-27.47 cm, chair width 29.13-34.54 cm, chairlength 35.80-39.87 cm, and chairback height 74.28-79.72 cm.Conclusion: It is necessary to make improvements to workstation of fish smoking workers in the coastalarea of Surabaya, as an attempt to make it ergonomic.